БІОБІБЛІОГРАФІЧНИЙ ПОКАЖЧИК ìДЕСЯТЬ РОКІВ УКРАЇНСЬКОЇ ЛІТЕРАТУРИ. 1917ñ1927î А. ЛЕЙТЕСА І М. ЯШЕКА: ПРЕДМЕТНА ГАЛУЗЬ І МОЖЛИВОСТІ ВИКОРИСТАННЯ В ГУМАНІТАРНИХ ДОСЛІДЖЕННЯХ (Zaporizhzhia Historical Review, 2021)
The article is devoted to the bibliographic index ìTen years of Ukrainian literature. 1917−1927î of A. Leites and M. Jashek. The author studies the content and the ways of the index in the humanities is used. The special attention is given to the methodical principles of the compiling the index.